Altered dynamic neural activities in individuals with obsessive-compulsive disorder and comorbid depressive symptoms - Shang, Tinghuizi; Chen, Yunhui; Ding, Zhenning; Qin, Weiqi; Li, Shancong; Wei, Siyi; Ding, Zhipeng; Yang, Xu; Qi, Jiale; Qin, Xiaoqing; Lv, Dan; Li, Tong; et al. (Frontiers in Psychiatry, 2024)
Depressive symptoms are the most prevalent comorbidity in individuals with obsessive-compulsive disorder (OCD). The objective of this study was to investigate the dynamic characteristics of restingstate neural activities in OCD patients with depressive symptoms. We recruited 29 OCD patients with depressive symptoms, 21 OCD patients without depressive symptoms, and 27 healthy controls, and collected data via structural and functional magnetic resonance imaging (fMRI). We analyzed the fMRI results using the dynamic a mplitude of low-frequency fluctuation (dALFF) and support vector machine (SVM) techniques. Compared with OCD patients without depressive symptoms, OCD patients with depressive symptoms exhibited an increased dALFF in the left precuneus and decreased dALFF in the right medial frontal gyrus. The SVM indicated that the integration of aberrant dALFF values in the left precuneus and right medial frontal gyrus led to an overall accuracy of 80%, a sensitivity of 79%, and a specificity of 100% in detecting depressive symptoms among OCD patients.Therefore, our study reveals that OCD patients with depressive symptoms display neural activities with unique dynamic characteristics in the resting state. Accordingly, abnormal dALFF values in the 2 left precuneus and right medial frontal gyrus could be used to identify depressive symptoms in OCD patients.